Oral mucositis severity in patient with head and neck cancer undergoing chemotherapy and/or radiotherapy - Dewi Oktafia Traktama; Irna Sufiawati (Majalah Kedokteran Gigi Indonesia, 2018)
Oral mucositis is an inflammatory process and ulcerative of the oral mucosa due to chemotherapy and/or radiotherapy. The incidence and severity of oral mucositis might be influenced by a variety of risk factors, related to the host and treatment of the cancer. This aim of the case report is to evaluate risk factors that affect the severity of oral mucositis in two patients with nasopharyngeal cancer undergoing chemotherapy and/or radiotherapy. The first case, oral mucositis grade III and oral candidiasis to a 54-year old woman undergoing 16 times radiotherapy for nasopharyngeal cancer stage IV. The second case, oral mucositis grade I and oral candidiasis were found in a 55-year old man suffering from nasopharyngeal cancer stage IV who has been treated 10 times with chemotherapy and radiotherapy. Both patients had a similar age range and cancer stage. The differences of severity oral mucositis in both cases were suspected due to the host factors-related that are gender and nutritional status. In addition, intra-oral condition (poor oral hygiene, xerostomia), smoking habits and patient compliance may also affect the severity of oral mucositis in the second case. Treatment factors such as the type, dose and duration of chemotherapy t, might also affect the severity in both cases. Both patients were given chlorhexidine gluconate 0.2%, nystatin oral suspension, vitamin B12, and folic acid for treating oral mucositis. In conclusion, the understanding of risk factors oral mucositis is deemed necessary to control the severity and to provide an appropriate management to improve the quality of patients’ life.